Identificación de especies de Candida y su resistencia a fluconazol en muestras respiratorias de pacientes hospitalizados en el Hospital General Reina del Cisne - Cueva Guajala, Xiomara Lissette (2022)
In the last years, an increase in the population of patients with risk of acquiring fungal infections such as yeasts of the genus Candida, whose various species can cause Candidiasis, this disease is a common systemic mycosis, with etiological agents, such as: C. albicans, C. tropicalis, C. parapsilosis, C. glabrata, C. guilliermondii and C. dubliniensis. According to its treatment, the treatment of choice is amphotericin B or fluconazole, in severe cases combined treatment with flucytosine. These microorganisms and their antifungal resistance constitute an important emerging health problem worldwide because they produce candidiasis and develop in patients with severe immunosuppression in hospital centers. This study is non-experimental and cross-sectional and has as an objective to identify Candida species and their resistance to fluconazole in respiratory samples from patients hospitalized at the Reina del Cisne General Hospital in the Piñas city. Through the use of Sabouraud Agar, chromogenic methods such as CHROMagar™ Candida and Mueller Hinton supplemented with glucose and methylene blue for antifungigram, 37 positive cultures for Candida spp. were isolated, Candida albicans being the most frequent in the hospitalization area with the 57.7% and Candida tropicalis in the Intensive Care Unit with the 81.8% respectively, predominantly Candida albicans in sputum samples and Candida tropicalis in tracheal secretions. Resistance to fluconazole was found in 50% for Candida albicans and the 50% for Candida tropicalis, respectively. Finally, its concluded that the use of chromogenic media such as CHROMagar™ Candida is useful in the presumptive identification of species of the genus Candida; the species Candida albicans is frequent in sputum samples from patients in the hospitalization area and Candida tropicalis is a nosocomial agent of the Intensive Care Unit frequent in samples of tracheal secretion, being the two species that expressed mechanisms of resistance to fluconazole